2021
DOI: 10.1037/spq0000423
|View full text |Cite
|
Sign up to set email alerts
|

School-wide social emotional learning and cyberbullying victimization among middle and high school students: Moderating role of school climate.

Abstract: Although the importance of social and emotional learning (SEL) competencies in bullying prevention has received increased recognition, limited research has examined youth's cyberbullying victimization (CBV) experiences through a school-wide SEL perspective. Guided by the school-wide SEL framework and the social-ecological model, this study examined the associations between students' perception of four core SEL competencies (i.e., responsible decision-making, social awareness, self-management, and relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
2
11
1
Order By: Relevance
“…The data obtained through the percentages of the answers show that the adolescents evaluated have, for the most part, social skills and that, in general, they had no experiences related to this type of cyberbullying (Tanrikulu and Erdur-Baker, 2019). This is consistent with previous studies, which indicate that having social skills is less frequent to become involved as a victim or stalker in situations of cyber violence (Bradbury et al, 2018;Acosta et al, 2019;Yang et al, 2021). Subsequently, the Spearman correlation test was applied to analyze the relationship between the six categories of the SSYI scale and the three factors of each subscale of the CSCRD.…”
Section: Discussionsupporting
confidence: 86%
“…The data obtained through the percentages of the answers show that the adolescents evaluated have, for the most part, social skills and that, in general, they had no experiences related to this type of cyberbullying (Tanrikulu and Erdur-Baker, 2019). This is consistent with previous studies, which indicate that having social skills is less frequent to become involved as a victim or stalker in situations of cyber violence (Bradbury et al, 2018;Acosta et al, 2019;Yang et al, 2021). Subsequently, the Spearman correlation test was applied to analyze the relationship between the six categories of the SSYI scale and the three factors of each subscale of the CSCRD.…”
Section: Discussionsupporting
confidence: 86%
“…Research evidence is consensual to show that socioemotional development is considered one of the predictors of positive outcomes both at school (e.g., academic achievement, and positive relationships with peers) and throughout life (e.g., social inclusion or integration into the labor market) [2,3]. Empirical evidence confirms that the implementation of SEL programs allows: (1) students' greater attitudinal adjustment and higher ability to effectively manage their difficulties; (2) increased academic achievement; (3) a reduction of emotional and behavioral problems and psychological distress; and (4) the promotion of more positive school environments, with a lower prevalence of bullying behaviors [4][5][6][7][8]. In particular, the promotion of socioemotional development, specifically the stimulation of skills related to self-control, empathy, and problem solving are associated with higher levels of motivation and school involvement, therefore enhancing academic success and preventing students from dropping out of school [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Anthony et al [17] found that 35% of their participants reported being a perpetrator of cyberbullying during the senior year of high school. Recent studies have found similar estimates of cyberbullying during high school [58][59][60][61][62], and, that outside of the COVID-19 pandemic school year where cyberbullying decreased [63,64], cyberbullying perpetration increases through middle school and then stabilizes through high school [7,37,60,61,[65][66][67]. These findings taken together suggest this upward trend continues beyond middle school, and that middle school and early high school may be the best time to intervene [15,[38][39][40][41]68].…”
Section: Discussionmentioning
confidence: 88%
“…Currently, there is no clear picture regarding the relationship between sex and cyberbullying perpetration and victimization [61]. For example, several studies have found that neither boys nor girls were especially more likely to take on the role of cyberbullying perpetrator or victim [17,38,61,71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation